Disclosure sustainability reporting and corporate governance business performance: how it impacts on market performance - Divine Prilly Yolanda; Fransiskus Eduardus DAROMES; Ana Mardiana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
This research proves empirically that the mechanism of corporate governance and sustainability report as a predictor of financial performance and its impact on market performance. The research model is built on the basis of stakeholder theory. This research uses purposive sampling method in sampling technique. The sample used in this study are non-financial companies listed on the Indonesia Stock Exchange in 2017-2019 which publish annual reports and sustainability reports, respectively. The results of this study indicate that both the disclosure of the sustainability report and the corporate governance mechanism have a positive and significant effect on financial performance. Financial performance has a positive and significant effect on market performance. Further findings indicate that corporate governance mechanisms affect market performance through financial performance. On the other hand, the disclosure of the sustainability report has no effect on market performance through financial performance.